The Effect of Mudharabah, Musyarakah, and Murabahah Financing on the Profitability Level of Islamic Commercial Banks in Indonesia - Lia Rachmawati; Diana Dwi Astuti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study pursuits to locate the effect of mudharabah, musyarakah, and murabahah financing at the profitability degree of Islamic industrial Banks in Indonesia within the 2015-2018 length. The populace on this have a look at there are 14 groups, and get three samples, particularly PT. bank Muamalat Indonesia, PT. BRI Syariah financial institution, and PT. Mandiri Syariah financial institution. This examine used a purposive sampling method in figuring out the pattern, while the records evaluation approach used more than one linear regression evaluation with the SPSS utility. The results of this observe suggest that the t-check indicates that partly mudharabah has a fine and insignificant effect on the extent of profitability, while musharaka has a poor and large impact on the extent of profitability, even as murabaha has a negative and insignificant impact on the profitability degree of Islamic business Banks in Indonesia. within the F test, the independent variable simultaneously has a enormous impact, but the adjusted R-square cost suggests the impartial variable in explaining the established variable by using 80%.